Generador de Grafos Multi-relacionales a partir de redes sociales - Almagro Blanco, Pedro; Ordoñez Salinas, Sonia (Ingeniería, 2014)
The tool introduced in this paper, CorpuRed, allows obtaining a dataset from online social networks that can be used for research projects that require information about social behaviour on Internet. The way to obtain such data is slightly platform dependent (the Facebook case is described) and they are stored in a graph database that will be accessible through an academic license API.